Unveiling zoonotic threats: molecular identification of Brugia sp. infection in a lion - Junsiri, Witchuta; Kamkong, Patchana; Phojun, Aunchisa; Taweethavonsawat, Piyanan (Frontiers in Veterinary Science, 2024)
Brugia malayi and B. pahangi, potential zoonotic pathogens transmitted by mosquitoes, are believed to primarily infect dogs and cats as reservoir hosts. Although previous studies have indicated nematode infections in lions, particularly in zoo environments where human contact with these reservoirs is possible, limited documentation exists regarding Brugia sp. infections in lions in Thailand. This study aims to investigate a case of Brugia infection in a lion from a zoo in Thailand.The blood sample was collected and examined from a female lion, using staining methods to morphologically identify microfilaria at the genus level. Subsequently, the PCR was employed targeting specific genes, including mitochondrial 12S rDNA, 18S rDNA, cytochrome oxidase I (COI) and Wolbachia surface protein (wsp), to confirm the species of the filarial nematode parasite.The genetic sequencing results revealed a high similarity (99-100%) to B. malayi for the 12S rDNA, 18S rDNA, COI and wsp genes. Phylogenetic analysis based on nucleotide sequences from the 12S rDNA, 18S rDNA, COI and wsp genes showed that the sequences from this study belong to different clusters. This marks the inaugural documentation of molecular identification of Brugia infection in a lion, signifying that lions could function as reservoirs for this parasite and present a potential public health risk in the region. Our research underscores the effectiveness of molecular techniques and phylogenetic analysis in discerning and comprehending the evolution of filarial parasites.Additionally, it emphasizes the significance of these methods in enhancing the diagnosis, control, and prevention of zoonotic filarial nematode infections.